2016
DOI: 10.3389/fimmu.2016.00205
|View full text |Cite
|
Sign up to set email alerts
|

A Subset of Patients with Acute Myeloid Leukemia Has Leukemia Cells Characterized by Chemokine Responsiveness and Altered Expression of Transcriptional as well as Angiogenic Regulators

Abstract: Acute myeloid leukemia (AML) is an aggressive and heterogeneous bone marrow malignancy, the only curative treatment being intensive chemotherapy eventually in combination with allogeneic stem cell transplantation. Both the AML and their neighboring stromal cells show constitutive chemokine release, but chemokines seem to function as regulators of AML cell proliferation only for a subset of patients. Chemokine targeting is therefore considered not only for immunosuppression in allotransplanted patients but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…Moreover in coculture experiments, AML patient-derived BMMSCs were found to be ubiquitously responsive to AML-derived MIF, which resulted in an increase in IL8 expression by the BMMSCs. This is in keeping with similar reports on other cytokine pathways, which have shown that BM-MSCs can constitutively express various chemokines (32), and AML cells are able to respond to these chemokines (32,33). In this study, we also examined the genotype of six BM-MSCs used for the experiments and found three of six to be normal and in other three, the genotyping failed (Supplementary Table S2).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover in coculture experiments, AML patient-derived BMMSCs were found to be ubiquitously responsive to AML-derived MIF, which resulted in an increase in IL8 expression by the BMMSCs. This is in keeping with similar reports on other cytokine pathways, which have shown that BM-MSCs can constitutively express various chemokines (32), and AML cells are able to respond to these chemokines (32,33). In this study, we also examined the genotype of six BM-MSCs used for the experiments and found three of six to be normal and in other three, the genotyping failed (Supplementary Table S2).…”
Section: Discussionsupporting
confidence: 89%
“…It appears that other mechanisms for chemotherapy resistance may be involved including normal cells, like macrophages, as shown by recent evidence. However, multiple mechanisms involving not only the CCL2/CCR2 axis but as Brenner et al suggested [38], the chemokine milieu is important in AML biology. To targetone or several chemokines may affect AML susceptibility to chemotherapy and help develop new therapies for AML in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines play a central role in the recruitment of cells involved in the induction of an immune-response (Brenner et al 2017;Brenner and Reikvam 2016;Karin and Wildbaum 2015). In cancer, chemokines are secreted by tumor cells, immune cells and stromal cells in the tumor microenvironment (Nagarsheth et al 2017).…”
Section: Role Of Chemokines In Tumor Immunology and In Immunotherapymentioning
confidence: 99%